Adult children of parents with mental illness: navigating stigma. Issue 1 (24th July 2015) - Murphy, Gillian; Peters, Kath; Wilkes, Lesley; Jackson, Debra
Abstract: The experiences of children who live with parental mental illness are becoming increasingly recognized. However, there remains a limited body of knowledge in relation to an individual's longer term experiences. This study sought adult children's experiences of childhood parental mental illness. It generated reflections of 13 adult children who had lived with parents with mental illness during their childhood. The narrative design of the study facilitated a voice for participants. The paper presents one main theme of the findings. The findings offer a unique insight into childhood awareness of social stigmas and children's behavioural changes to avoid disclosure of parental mental illness. Participants noted that they were aware of social stigmas associated with mental illness during their childhood. This contributed to their fear of disclosure to others that fuelled a culture of familial secrecy, reinforcing the children's own sense of difference. Further work is required to enhance community understanding about the familial journeys of parental mental illness and the impact of negative‐natured stigmas.